Determination of fetal weight by ultrasonographic evaluation of fetal mid-thigh soft-tissue thickness in late third trimester - Lynn Joy; Anil Kumar Sakalecha; Rajeswari G; Varshitha GR; Surya Kanth Anne; Shantala Sawkar (Asian Journal of Medical Sciences, 2023)
Background: Estimation of fetal weight is of utmost importance in the planning and management of uneventful labor. This study was done to compare the estimated fetal weight determined by Hadlock’s method and Scioscia’s formula (using femur length and mid-thigh soft-tissue thickness [MTSTT]) to the actual birth weight (ABW). Aims and Objectives: The objectives of this study were as follows: (1) To estimate fetal weight by Hadlock’s method and ultrasonographic evaluation of fetal MTSTT in late third trimester. (2) To correlate fetal weight derived by Hadlock’s method and ultrasonographic evaluation of fetal MTSTT with ABW. Materials and Methods: The study was conducted during the period November 2022–January 2023, at Sri Devaraj Urs Medical College, Tamaka, Kolar. Seventy-six pregnant ladies at term (between 37 and 40 weeks) were included in the study. Results: This study assessed validity of Hadlock formulae and Scioscia’s formulae for detecting fetal weight. For detection of fetal weight by Hadlock’s method, area under curve (AUC) was 0.961 and according to Scioscia’s formulae, AUC was 0.965. This study showed good agreement between fetal weight derived by Hadlock formulae and actual fetal weight (Kappa value – 0.725). There was also good agreement between fetal weight derived by Scioscia’s formulae and actual fetal weight (Kappa value – 0.745). Conclusion: The fetal weight derived by Scioscia’s formula was comparable to the actual fetal weight allowing us to rely on Scioscia’s formulae to detect fetal weight. Calculating fetal weight by measurement of fetal MTSTT serves as an additional tool for estimation of fetal weight along with the existing parameters, thereby increasing the likelihood for accurate fetal weight estimation.